Long-term metastability of light-induced defects in hydrogenated amorphous silicon. (3rd May 2016) - Morigaki, Kazuo; Hikita, Harumi; Ogihara, Chisato
Abstract: The decay of the peak intensity of the electron spin resonance signal associated with light-induced dangling bonds in a-Si(H) has been measured at room temperature as a function of time during very long intervals such as 3400 days after the intense pulsed illumination was turned off. The decay curve is fitted by an exponential function with a decay constant of 393 days and reaches a steady-state value smaller than the value taken before illumination. Such a long-term metastability of light-induced dangling bonds in a-Si:H is discussed in terms of reconstruction of the amorphous network occurring through hydrogen motion.